Antenatal Betamethasone for Women at Risk for Late Preterm Delivery. Issue 8 (August 2016) - Gyamfi-Bannerman, Cynthia; Thom, Elizabeth A.; Blackwell, Sean C.; Tita, Alan T. N.; Reddy, Uma M.; Saade, George R.; Rouse, Dwight J.; McKenna, David S.; Clark, Erin A. S.; Thorp, John M.; Chien, Edward K.; Peaceman, Alan M.; et al.
Abstract : (Abstracted from N Engl J Med 2016;374:1311–1320) Infants born during the late preterm period (34 weeks 0 days to 36 weeks 6 days) are more likely to suffer neonatal and childhood complications than newborns born at term (37 weeks or later). A randomized, multicenter trial was undertaken (between 2010 and 2015) at 17 university-based clinical centers participating in the Maternal-Fetal Medicine Units Network of the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) to assess whether the administration of betamethasone to women who are likely to deliver in the late preterm period would decrease the risks of neonatal morbidities.